2003
DOI: 10.1001/archotol.129.9.966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lacrimal and Salivary Gland Involvement in Sjögren's Syndrome

Abstract: The rose bengal score remains the eye test of choice, as it has the highest specificity for SS. Hyperglobulinemia and especially positive serologic findings for SS-B may warrant close monitoring of the eyes, since these serum findings appear to relate to the severity of ocular surface damage. Parotid sialography and stimulated secretion of SM/SL saliva are more specific in diagnosing SS than unstimulated secretion of whole saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
7
8
0
Order By: Relevance
“…Researchers have made repeated attempts to determine the relationship between prognostic factors and ocular manifestations in SS. Toker et al 3 found a significant correlation between tear anti-La/SSB concentrations and rose bengal staining scores, and Vissink et al 17 demonstrated a positive correlation between the presence of La/SSB autoantibody in serum and rose bengal staining scores, which corresponds well with our results. The present study shows that a significant elevation of Ro/SSA and La/SSB autoantibodies in the sera of moderate to severe KCS in SS.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers have made repeated attempts to determine the relationship between prognostic factors and ocular manifestations in SS. Toker et al 3 found a significant correlation between tear anti-La/SSB concentrations and rose bengal staining scores, and Vissink et al 17 demonstrated a positive correlation between the presence of La/SSB autoantibody in serum and rose bengal staining scores, which corresponds well with our results. The present study shows that a significant elevation of Ro/SSA and La/SSB autoantibodies in the sera of moderate to severe KCS in SS.…”
Section: Discussionsupporting
confidence: 92%
“…Although the vital staining exhibited the highest likelihood ratio in this study, in agreement with previous works that indicated vital dye score the test of choice, 21 the complessive diagnostic performance was scarce in our study, as it can be seen in the ROC plot analysis flat curve, probably as a consequence of a bias in data collection, since vital dye staining was applied only to those patients with Fluo negative corneas.…”
Section: Eyesupporting
confidence: 89%
“…The median value of PFR in the MALT‐L group was reduced compared with the SS‐low risk subgroup. UWSFR and PFR showed a strong correlation ( r = 0.6, p < 0.0001) in concordance to Kalk, Mansour, et al () and Vissink et al () ( r = 0.75, p < 0.001). However, it appears that parotid gland involvement is more evident in later stages of SS when there may be little correlation between whole mouth and parotid flow rates.…”
Section: Discussionsupporting
confidence: 86%